2021
DOI: 10.3389/fimmu.2021.740540
|View full text |Cite
|
Sign up to set email alerts
|

IL-17+ Mast Cell/T Helper Cell Axis in the Early Stages of Acne

Abstract: Acne is a multifactorial disease driven by physiological changes occurring during puberty in the pilosebaceous unit (PSU) that leads to sebum overproduction and a dysbiosis involving notably Cutibacterium acnes. These changes in the PSU microenvironment lead to a shift from a homeostatic to an inflammatory state. Indeed, immunohistochemical analyses have revealed that inflammation and lymphocyte infiltration can be detected even in the infraclinical acneic stages, highlighting the importance of the early stage… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…Hyperkeratotic plugs composed of corneocytes in the lower portion of the follicular infundibulum create a new environment that impacts the microbiota and fosters proliferation of a gram-positive bacillus, Cutibacterium acnes . IL-17A-producing mast cells were detected in the perifollicular area of acne vulgaris lesions ( 23 ). Activated memory/effector CD4 + T cells induced IL-17A production by human mast cells, implying a contribution of mast cells to development of acne vulgaris ( 23 ).…”
Section: Mast Cells In Skin Inflammation During Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperkeratotic plugs composed of corneocytes in the lower portion of the follicular infundibulum create a new environment that impacts the microbiota and fosters proliferation of a gram-positive bacillus, Cutibacterium acnes . IL-17A-producing mast cells were detected in the perifollicular area of acne vulgaris lesions ( 23 ). Activated memory/effector CD4 + T cells induced IL-17A production by human mast cells, implying a contribution of mast cells to development of acne vulgaris ( 23 ).…”
Section: Mast Cells In Skin Inflammation During Infectionmentioning
confidence: 99%
“…IL-17A-producing mast cells were detected in the perifollicular area of acne vulgaris lesions ( 23 ). Activated memory/effector CD4 + T cells induced IL-17A production by human mast cells, implying a contribution of mast cells to development of acne vulgaris ( 23 ). However, their precise role remains unclear.…”
Section: Mast Cells In Skin Inflammation During Infectionmentioning
confidence: 99%
“…Additionally, the IFN-γ-induced chemokines—CXCL9, CXCL10, and CXCL11—are overexpressed ( 42 ). The combined expression of CXCR3 and CD161 was present in 15% of conventional T cells, reminiscent of pathogenic Th17.1 lymphocytes ( 43 ). Cutibacterium acnes can trigger the concomitant production of IL-17 and IFN-γ ( 44 ).…”
Section: Key Mechanisms Of Functional Cell Plasticitymentioning
confidence: 99%
“…Specific anti- C. acnes activate complement and recruit neutrophils ( Dreno et al, 2015 ). CD4 + T cells were also found in patches of acne where they exacerbate inflammation ( Agak et al, 2014 ; Kelhälä et al, 2014 ; Kistowska et al, 2014 ; Eliasse et al, 2021 ). An exploration of roles and mechanisms of GM Trp metabolism in mediating innate immune inflammation and sebaceous gland function during acne vulgaris pathology follows ( Figure 1 ).…”
Section: Microbial Tryptophan Metabolites May Regulate Innate and Ada...mentioning
confidence: 99%
“…T lymphocytes have been demonstrated to appear first in early acne lesions ( Norris and Cunliffe, 1988 ; Jeremy et al, 2003 ) and IL-17-producing cells with increased IL-17A tissue expression have also been found in lesions ( Agak et al, 2014 ; Kistowska et al, 2014 ). Activation of mast cells to produce IL-17 in CD4 + T cell rich areas has been suggested, even in the subclinical stages of acne ( Eliasse et al, 2021 ), and scattered distribution of IL-17A positive cells was observed in both the papillary dermis and around sebaceous follicles in acne lesions ( Kelhälä et al, 2014 ).…”
Section: Microbial Tryptophan Metabolites May Regulate Innate and Ada...mentioning
confidence: 99%